An Analysis Of Politeness Strategies Used By Fifth Semester Students At Undikma - Wahyudiantari, Ni Wayan Prami (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
This research aimed to determine the politeness strategies used by fifth semester students at UNDIKMA. The research was conducted through a qualitative descriptive method. Qualitative descriptive method was used in analyzing the data because it will be explained with words, phrases, and sentences. The data based on the utterances of the fifth semester students at UNDIKMA. In collecting data, the researcher used observational and non-participatory methods, taking notes. The pragmatic identity method is applied in analyzing the data. The theory used to explain the analysis of politeness strategies is the theory of Brown and Levinson (1987). There are four politeness strategies classified by Brown and Levinson, namely Bald on Record, Positive Politeness, Negative Politeness and Off Record.The researcher found four politeness strategies used by fifth semester students at UNDIKMA. The result indicated that were Bald on Record, Positive Politeness, Negative Politeness and Off Record. The most dominant politeness strategy used was Positive Politeness. Another dominant politeness strategy used was Bald on Record, Negative Politeness and the last one is Off Record.